1980
DOI: 10.1210/endo-107-4-1176
|View full text |Cite
|
Sign up to set email alerts
|

Somatogenic Receptors of Rat Liver: Regulation by Insulin*

Abstract: Somatogenic (i.e. GH) receptors have been studied on liver microsomal membranes from male and female rats. Tracer bovine GH was displaced from its binding sites by GHs of various species, but was displaced only weakly by PRLs. Specific bovine GH binding was 3.5-fold higher to female rat liver membranes than to membranes from males. Streptozotocin-induced diabetes significantly reduced binding, by 80% in females and 50% in males, while insulin therapy to normalize weight gain reversed the decrease in binding. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
96
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(105 citation statements)
references
References 32 publications
8
96
0
1
Order By: Relevance
“…Regulation of rat liver GH receptors by testosterone has not been documented, although it has been reported that females have more receptors than males [1,12,13]. Our studies confirm that testosterone decreases PRL receptors, and they establish a similar role for testosterone on GH binding in the livers of female rats.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Regulation of rat liver GH receptors by testosterone has not been documented, although it has been reported that females have more receptors than males [1,12,13]. Our studies confirm that testosterone decreases PRL receptors, and they establish a similar role for testosterone on GH binding in the livers of female rats.…”
Section: Discussionsupporting
confidence: 80%
“…Although the nonspecific binding of bGH tracer was high relative to the specific binding, this figure is comparable to that seen in other published studies of bGH binding to microsomal membranes [1,14], homogenates [5] and hepatocyte pellets [12]. The bGH for iodination (S-…”
Section: (N =8)supporting
confidence: 87%
See 3 more Smart Citations